2013
DOI: 10.1890/12-1490.1
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic diet shifts promote predator‐mediated coexistence

Abstract: Ontogenetic diet shifts promote predator-mediated coexistenceWollrab, S.; de Roos, A.M.; Diehl, S. Published in: Ecology DOI:10.1890/12-1490.1 Link to publication Citation for published version (APA):Wollrab, S., de Roos, A. M., & Diehl, S. (2013). Ontogenetic diet shifts promote predator-mediated coexistence. Ecology, 94(12), 2886-2897. DOI: 10.1890/12-1490.1 General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…Efforts should now be made to confirm or refute this by examining the size and mode of feeding of newly settled juveniles of L. heros directly under laboratory and field conditions. Understanding how prey preference and diet change across a predatorÕs life span, from newly metamorphosed juvenile to adult, is essential to understanding community-wide effects of predators in various systems (Wollrab et al 2013). Muricid gastropods can shift between preferred prey species depending on prey abundance, and will remain selecting the latter prey species even if the former rebounds and becomes abundant again (e.g., Wood 1968, Murdoch 1969.…”
Section: Ontogenetic Changes In Diet: Intraspecific Size Selectivity mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts should now be made to confirm or refute this by examining the size and mode of feeding of newly settled juveniles of L. heros directly under laboratory and field conditions. Understanding how prey preference and diet change across a predatorÕs life span, from newly metamorphosed juvenile to adult, is essential to understanding community-wide effects of predators in various systems (Wollrab et al 2013). Muricid gastropods can shift between preferred prey species depending on prey abundance, and will remain selecting the latter prey species even if the former rebounds and becomes abundant again (e.g., Wood 1968, Murdoch 1969.…”
Section: Ontogenetic Changes In Diet: Intraspecific Size Selectivity mentioning
confidence: 99%
“…Using theoretical models, Wollrab et al (2013) showed that small changes in diet between juvenile and adult predators can shift mechanisms of predator-mediated coexistence among predators and prey within an ecological community. Although these shifts can potentially promote coexistence and biodiversity, they can also introduce alternative states within ecological communities, in which slight disturbances can lead to depauperate communities (Wollrab et al 2013). Without the knowledge of dietary changes across the ontogeny of naticid gastropods, assessments of whole-community impacts of naticid predation have to assume uniform predatory behavior across all sizes and ages of these predators.…”
Section: Ontogenetic Changes In Diet: Intraspecific Size Selectivity mentioning
confidence: 99%
“…These ontogenetic niche shifts may have widespread effects on population and community dynamics (de Roos & Persson 2013), such as promoting the coexistence of competitors (Wollrab et al 2013), reducing the stabilizing effects of ecosystem complexity (Rudolf & Lafferty 2011), and even altering the strength of trophic cascades (Rudolf & Rasmussen 2013). Variations in trophic interactions as a result of ontogenetic niche shifts are beginning to be considered in experimental and modeling food web studies (van Leeuwen et al 2014), but there are few empirical examples of variation in species ontogeny in field settings across large geographic scales.…”
Section: Introductionmentioning
confidence: 99%
“…Third, species could differ in terms of where they use their resources, thereby exhibiting spatial niche partitioning (May and Hassell 1981;Chesson 2000). Food partitioning in regard to time and space seems to play an important role in reef fish coexistence (Armstrong and McGehee 1980;Pimentel and Joyeux 2010;Wollrab et al 2013) by reducing competition levels on sympatric species (Nithirojpakdee et al 2012). …”
mentioning
confidence: 99%